The use of anti-tumour necrosis factor therapy in HIV-positive individuals with rheumatic disease. Issue 5 (13th December 2007) - Cepeda, E J; Williams, F M; Ishimori, M L; Weisman, M H; Reveille, J D
Abstract : Objective: The purpose of this study was to examine the safety and efficacy of anti-tumour necrosis factor (TNF) agents (etanercept, infliximab and adalimumab) in HIV-positive patients with rheumatic diseases refractory to standard therapy. Methods: Patients were treated with anti-TNF blocker with rheumatic diseases refractory to disease modifying antirheumatic drugs who had a CD4 count of >200 mm3 and an HIV viral load of <60 000 copies/mm3 and no active concurrent infections. Changes in CD4 counts, HIV viral loads, or other adverse effects while on anti-TNF agents and clinical response were monitored for 28.1 (SD 20.9) months (range 2.5–55). Results: Eight HIV-positive patients were treated with anti-TNF blockers (two patients with rheumatoid arthritis, three with psoriatic arthritis, one with undifferentiated spondyloarthritis, one with reactive arthritis and one with ankylosing spondylitis). No significant clinical adverse effect was attributed to this treatment in any patient. CD4 counts and HIV viral load levels remained stable in all patients. Three patients on etanercept therapy and two patients on infliximab had sustained clinical improvement in their rheumatic diseases. Conclusions: This retrospective series of eight patients suggests that treatment with anti-TNF-α therapy is a viable alternative in HIV patients without advanced disease with associated rheumatic diseases refractory to standard therapy.